Impact of Mg rich synthetic gypsum application on the environment and palm oil quality - A. R., Sahibin; Jusop, Shamsuddin; Ishak, Che Fauziah; Othman, Radziah; I., Wan Mohd Razi; Mohd Sufian Kang, Enio Kang (Elsevier BV, 2019)
A study was conducted in an oil palm plantation in Peninsular Malaysia to elucidate the effects of applying Magnesium Rich Synthetic Gypsum (MRSG), a by-product of chemical plant, on the chemical properties of soil, the uptake of heavy metals by the palm trees, the oil quality and its impact on the surrounding environment. The results showed that MRSG application onto soil cropped to oil palm could bring positive impact in terms of soil chemical properties and oil palm production. The quality of the oil was not significantly affected by the continuous MRSG application as shown by the low heavy metals and trace elements of concern content (Cu: 0.062 mg/kg; Fe: 2.10 mg/kg; Mn: 1.93 mg/kg; Pb: 0.006 mg/kg; Zn: 0.103 mg/kg; Cr: 0.354 mg/kg; Ni: 0.037 mg/kg). From the I-geochem index, the soil was found to have values ranging from -3.81 to -1.03 which is considered as uncontaminated. Further, its application did not result in negative impact on the surrounding environment; hence, the quality of the soil and surface water in the plantation and/or the surrounding area remained intact. Phytotoxic elements in the oil palm tissue (As: 0.12 mg/kg; Se: 0.05 mg/kg; Zn: 1.48 mg/kg; Ce: 0.47 mg/kg; La: 0.26 mg/kg; Sr: 3.03 mg/kg) and cytotoxic elements in the oil were below the acceptable limit. Based on the results of the Environmental Monitoring out during the period of the study, it was concluded that application of the by-product of the chemical plant as a source of Mg to enhance soil fertility in the oil palm plantation was considered safe and sustainable. The effects of applying MRSG and Chinese kieserite was almost similar. So, MRSG can be used as a possible source of Mg to replace Chinese kieserite for oil palm production on the Ultisols in Peninsular Malaysia.